Influence of Agroforestry and Traditional Management of Maize (Zea mays L.) on Soil Fertility - Bertalot, Maria J. A.; Guerrini, Iraê Amaral [UNESP]; Mendoza, Eduardo; Pinto, Mauro S. V. (Taylor & Francis, 2013)
The aim of the work was to evaluate soil nutrient concentration at 0-5, 5-10, and 10-20 cm in maize (Zea mays L.) grown in sequence with black oats (Avena strigosa Schreb.) under Leucaena diversifolia alley cropping agroforestry system (AFS) and traditional management system/sole crop (without trees-TS), following a randomized block design. The experiment was carried out at the Brazilian Association of Biodynamic Agriculture, in Botucatu, São Paulo, Brazil. The treatments were: control (C), chemical fertilizer (F), biomass of L. diversifolia alley cropping (B), and biomass of L. diversifolia alley cropping + chemical fertilizer (B+F). After 2 yr, it was observed that pH, organic matter, and nutrient content had a tendency to show higher values in the treatments biomass+fertilizer, biomass, and fertilizer application, in both systems. Higher values in pH, organic matter, phosphorus, potassium, calcium, magnesium, sum of bases, cation exchange capacity, percentage base saturation, boron, copper, and manganese tended to occur in the agroforestry system. © 2013 Copyright Taylor and Francis Group, LLC.
Keywords: alley cropping; crop sequence; green manure; Leucaena diversifolia; soil nutrient concentration; soil organic matter; Alley cropping; Crop sequences; Green manures; Leucaena; Soil nutrients; Soil organic matters; Biogeochemistry; Biological materials; Biomass; Crops; Forestry; Grain (agricultural product); Manures; Organic compounds; Soils; Fertilizers; agroforestry; concentration (composition); cropping practice; forest management; maize; manure; soil fertility; soil nutrient; traditional knowledge